Design and analysis of zero-voltage switching for boost converters - Srinidhi Sundara Narayanan (Nanyang Technological University, 2024)
Power electronic converters form an integral and indispensable component of wide array of systems ranging from electronic devices to electric vehicle, power systems etc. With rapid technological advancement in electronic devices and appliances there is a demand for converters with high efficiency and higher power packing density. In order to increase the power packing density, switching frequency must be increased which results in reduction of size of the components and hence the improvement in power packing density. Conventional converters based on PWM still find widespread use in low and medium-power applications. However, the rectangular waveforms of PWM cause turn on and turn off losses in these solid-state switches which limit the operating frequency. Additionally, the rectangular PWM waveforms comprise of wide spectrum of harmonics and the resulting electromagnetic interference can hamper the functioning of circuits in the vicinity. In order to solve the aforementioned problems, resonant converters were developed by incorporating an auxiliary resonant circuit in the conventional PWM based DC-DC converters. This thesis intends to present a thorough analysis and design of the ZVS boost converter by outlining how the integrated resonant circuit enables soft switching conditions for the switches, while also reducing the overlap of voltage and current. As a result, switching losses are mitigated.